Barriers to Accessing Secondary Education in India (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Access to secondary education in India remains a significant challenge, particularly for marginalized communities. Despite numerous government initiatives and policies aimed at enhancing educational opportunities, socio-economic disparities, geographical barriers, and issues related to the quality of education continue to hinder progress. This paper explores the various challenges faced in accessing secondary education in India, analyzing the socio-economic, geographical, and policy-related factors that contribute to the problem. It also examines government initiatives and their impact, using case studies to highlight areas of success and persistent challenges. The paper concludes with recommendations for improving access to secondary education through inclusive policies, community involvement, private sector participation, and the use of technology. Ensuring equitable access to secondary education is crucial for India's socio-economic development and the empowerment of its youth.